‘‘Effectiveness Of Progressive Muscle Relaxation Therapy And Guided Imagery On Functional Well Being, Selected Physical And Psychological Parameters Among Cancer Patients Receiving Chemotherapy’’. Evaluation Of Pilot Study (Journal of Pharmaceutical Negative Results, 2023)
Background: To test the effectiveness of progressive muscle relaxation therapy (PMR) and guided imagery (GI) as effects on physical and psychological parameters reducing interventions in patients with cancer who undergo chemotherapy. Methods: Patients were randomly assigned to the groups either control group or the intervention group (PMR and GI). Patients were observed for a total duration of 4 weeks and assessed with the standardised tools for physical and psychological parameters. (Trial registration number: CTRI/2021/12/038985.Results: According to inclusion criteria 15 patients were randomised to the control group and 15 to the intervention group. Intervention’s mean functional assessment of cancer therapy score, Pain score, nausea and vomiting score, anxiety score and stress score changes were significantly different compared to the control group.Conclusions: The findings showed that patients with cancer undergoing chemotherapy treatment can benefit from PMR and GI sessions to reduce their functional assessment of cancer therapy, physical and psychological parameters.